Personal attitudes toward time: The relationship between temporal focus, space‐time mappings and real life experiences. Issue 3 (6th March 2017) - Li, Heng; Cao, Yu
Abstract : What influences how people implicitly associate "past" and "future" with "front" and "back?" Whereas previous research has shown that cultural attitudes toward time play a role in modulating space‐time mappings in people's mental models (de la Fuente, Santiago, Román, Dumitrache & Casasanto, 2014), we investigated real life experiences as potential additional influences on these implicit associations. Participants within the same single culture, who are engaged in different intermediate‐term educational experiences (Study 1), long‐term living experiences (Study 2), and short‐term visiting experiences (Study 3), showed their distinct differences in temporal focus, thereby influencing their implicit spatializations of time. Results across samples suggest that personal attitudes toward time related to real life experiences may influence people's space‐time mappings. The findings we report on shed further light on the high flexibility of human conceptualization system. While culture may exert an important influence on temporal focus, a person's conceptualization of time may be attributed to a culmination of factors.